Deciphering the Role of Circadian Clock in Inflammatory Response and Immune Disorders Using Model Checking and Petri Nets - Hafeez Ur Rahman; Jamil Ahmad; Ainur Akhmediyarova; Dina Oralbekova; Orken Mamyrbayev (IEEE Access)
Circadian rhythms play a significant role to optimize immunity and combat infections. Any disturbance of the circadian clock, which is caused by environmental cues or zeitgebers, influences immune system’s performance. This interplay has encouraged research on possible novel treatment approaches for auto-immune diseases. The study aims to construct a Petri net model to analyze the implications of jet lag on the circadian rhythm and its potential involvement in the immune response and the associated diseases. First, the regulatory mechanism of the circadian-immune network is qualitatively modeled using GINsim tool. This model deciphers the roles of critical biological entities of the network and their interactions in the immune response. Then, the GINsim model is converted to a Petri net model, which facilitates the modeling of temporal dynamics of immune responses under circadian control. The simulation results indicate that the disruption of the circadian clock dampens the immune response by approximately 50%, emphasizing the necessity of circadian integrity. The results also predicted that RORs and REVERBA can be used to modulate immune responses. The simulation results show that the reverse effect of RORs on circadian oscillation is less than the REVERBA in modulating immune responses.